"Open the door to something better": Prof Ursula Keller on the challenges of being a woman in STEM – in Europe and abroad. Issue 4 (1st September 2022) - Moglia, Francesca
Abstract: The first tenured woman physics professor at ETH Zurich, and a career‐long campaigner for fair play and a level playing field for women in science, Ursula Keller, talks to Francesca Moglia, EPIC's former photonics technologies program manager.